Exaggerated Interventricular Dependence among Trauma and Burn Patients: A Relationship with Kidney Function—An Exploratory Study. Issue 4 (April 2019) - Younan, Duraid; Pigott, David C.; Richman, Joshua; Gibson, C. Blayke; Gullett, John P.; Pittet, Jean-Francois; Zaky, Ahmed
Acute kidney injury (AKI) is a serious condition that affects critically ill patients admitted to the ICU. In this study, we report the association between right ventricle shape and AKI in a cohort of burn and trauma patients. This study is a retrospective review of trauma and burn patients who were admitted to our ICU between 2013 and 2016 who underwent hemodynamic transesophageal echocardiography. Left ventricular eccentricity index (LVEI) measurements were performed on still images obtained from transgastric short-axis view clips at end diastole. LVEI was used as a surrogate of right ventricular volume loading. There were 132 patients, the mean age was 50.8 years, and they were predominantly white and males. Using logistic regression and adjusting for age, race, gender, injury mechanism, and injury severity, higher LVEI was independently significantly associated with lower incidence of AKI (odds ratio 0.03, confidence interval 0.00–0.69). Higher LVEI is associated with a lower incidence of AKI in critically injured trauma and burn patients.